Peritoneal dialysis peritonitis by anaerobic pathogens: a retrospective case series - Chao, Chia-Ter (BioMed Central, 2013)
BACKGROUND: Bacterial infections account for most peritoneal dialysis (PD)-associated peritonitis episodes. However, anaerobic PD peritonitis is extremely rare and intuitively associated with intra-abdominal lesions. In this study, we examined the clinical characteristics of PD patients who developed anaerobic peritonitis. METHODS: We retrospectively identified all anaerobic PD peritonitis episodes from a prospectively collected PD registry at a single center between 1990 and 2010. Only patients receiving more than 3 months of PD were enrolled. We analyzed clinical features as well as outcomes of anaerobic PD peritonitis patients. RESULTS: Among 6 patients, 10 episodes of PD-associated peritonitis were caused by anaerobic pathogens (1.59% of all peritonitis episodes during study the period), in which the cultures from 5 episodes had mixed growth. Bacteroides fragilis was the most common species identified (4 isolates). Only 3 episodes were associated with gastrointestinal lesions, and 4 episodes were related to a break in sterility during exchange procedures. All anaerobic pathogens were susceptible to clindamycin and metronidazole, but penicillin resistance was noted in 4 isolates. Ampicillin/sulbactam resistance was found in 2 isolates. In 5 episodes, a primary response was achieved using the first-generation cephalosporin and ceftazidime or aminoglycoside. In 3 episodes, the first-generation cephalosporin was replaced with aminoglycosides. Tenckhoff catheter removal was necessary in 2 episodes. Only one episode ended with mortality (due to a perforated bowel). CONCLUSION: Anaerobic PD-associated peritonitis might be predominantly caused by contamination, rather than intra-abdominal events. Half of anaerobic PD-associated peritonitis episodes had polymicrobial growth. The overall outcome of anaerobic peritonitis is fair, with a high catheter survival rate.